Validity of Assessment Attitude and Values System Based on Indonesian National Qualification Framework on Process Evaluation and Biological Learning Outcomes - Siska Nerita; Annika Maizeli; Aulia Afza (Postgraduate, University of Mataram, 2020)
In the subject of the Evaluation of Process and Outcome of Biological Learning (EPOBL), carried out by applying guided discovery methods and the use of handout based on guided discovery. Problems found in the lecture process are pre-existing assessments that are not in accordance with the lecture process with guided discovery methods that use handouts based on guided discovery. The purpose of this study is to produce an assessment based on the Indonesian National Qualifications Framework that valid in the EPOBL subject. This research is a development research using the Plomp model. The instrument used is a questionnaire validity assessment of attitude and values system. The data analysis technique uses the percentage formula. The results of the study showed that the value of the attitude and values system assessment was 95.83% with very valid criteria. It can be concluded that the assessment of attitudes and values system based on the Indonesian National Qualifications Framework in Process evaluation and biology learning outcomes is very valid